Al-Bunāwiyyah Ash-Shakliyyah fī Shi‘r ar-Rithā’ li-Abī Isḥāq Ibrāhīm bin ‘Ubaid Yāsīn lil-Andalus: Formalist Structuralism in the Elegy Poetry of Abu Ishaq Ibrahim Bin Ubaid Yasin for Andalusia - Nurchalis; Mawaddah Rizkima; Rasyad; Suraiya (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2025)
Poetry is a literary work that prioritizes the beauty of language and the density of meaning. To understand the meaning, an approach is needed to analyze the intrinsic elements in the poem. The approach used in this article is a formalist structuralism approach which will explain every intrinsic element contained in poetry, such as theme, language style, message, and so on. This research is a qualitative descriptive study because the researcher carried out analysis using two techniques, namely reading and note-taking techniques. The reading technique is carried out by reading and understanding each line of poetry in the poem and the note-taking technique is carried out by recording the research results after the researcher understands the meaning contained in the poetry text. The object of this research is the poem Ritsa' written by the poet Abi Ishaq Ibrahim Bin 'Ubaid Yasin for Andalusia, which is a poem containing the poet's lament about the era of the destruction of Islam in Andalusia. The results obtained are the theme of the poet's lament regarding his deep sadness towards Andalusia. Feelings of sadness and concern about what happened in Andalusia. The imagination contained in the poetry text is as if Andalusia is experiencing a serious disease which means extraordinary destruction that can wipe out Islam from the land of Andalusia. The language styles found in poetry are hyperbole, antonomasia, personification, rhetoric, oxymoron, parallelism, pleonasm, exclamation, allonym, symbolic, and tashbih. Apart from that, Wazan, qafiyah, diction, symbols, tone, message and the relationship between elements in poetry are obtained. الشعر عمل أدبي يعطي الأولوية لجمال اللغة وكثافة المعنى. لفهم المعنى، هناك حاجة إلى نهج لتحليل العناصر الجوهرية في القصيدة. النهج المستخدم في هذه المقالة هو النهج البنيوي الشكلي الذي سيشرح كل عنصر جوهري موجود في الشعر، مثل الموضوع، وأسلوب اللغة، والرسالة، وما إلى ذلك. يعد هذا البحث دراسة وصفية نوعية لأن الباحث قام بالتحليل باستخدام تقنيتين هما تقنيات القراءة وتدوين الملاحظات. وتتم تقنية القراءة من خلال قراءة وفهم كل سطر من الشعر في القصيدة، وتتم تقنية تدوين الملاحظات من خلال تسجيل نتائج البحث بعد أن يفهم الباحث المعنى الوارد في النص الشعري. موضوع هذا البحث هو قصيدة رتسا للأندلس للشاعر أبي إسحاق إبراهيم بن عبيد ياسين، وهي قصيدة تحتوي على رثاء الشاعر في عصر خراب الإسلام في الأندلس. وكانت النتائج المتحصل عليها موضوع رثاء الشاعر لحزنه العميق على الأندلس. مشاعر الحزن والقلق إزاء ما حدث في الأندلس. والخيال الذي يتضمنه النص الشعري وكأن الأندلس تعاني من مرض خطير يعني دماراً غير عادي يمكن أن يمحو الإسلام من أرض الأندلس. أنماط اللغة الموجودة في الشعر هي المبالغة، والتشريح، والتجسيد، والبلاغة، والتناقض، والتوازي، والحشو، والتعجب، والمجاز، والرمزي، والتشبيه. ويحصل فيما عدا ذلك على الوزان والقافية والإلقاء والرموز والنبرة والرسالة والعلاقة بين العناصر في الشعر Puisi adalah karya sastra yang mengutamakan keindahan bahasa dan kepadatan makna. Untuk memahami maknanya, diperlukan suatu pendekatan untuk menganalisis unsur intrinsik dalam puisi. Pendekatan yang digunakan dalam artikel ini adalah pendekatan strukturalisme formalis yang akan menjelaskan setiap unsur intrinsik yang terdapat dalam puisi, seperti tema, gaya bahasa, pesan, dan sebagainya. Penelitian ini merupakan penelitian deskriptif kualitatif karena peneliti melakukan analisis dengan menggunakan dua teknik, yaitu teknik membaca dan teknik mencatat. Teknik membaca dilakukan dengan membaca dan memahami setiap baris puisi dalam karya tersebut, sedangkan teknik mencatat dilakukan dengan mencatat hasil penelitian setelah peneliti memahami makna yang terkandung dalam teks puisi. Objek penelitian ini adalah puisi Ritsa’ yang ditulis oleh penyair Abu Ishaq Ibrahim Bin Ubaid Yasin untuk Andalusia, yaitu sebuah puisi yang berisi ratapan penyair tentang masa kehancuran Islam di Andalusia. Hasil yang diperoleh adalah tema ratapan penyair mengenai kesedihan mendalam terhadap Andalusia, perasaan sedih dan keprihatinan terhadap apa yang terjadi di sana. Imaji yang terdapat dalam teks puisi ini menggambarkan seolah-olah Andalusia mengalami penyakit parah, yang berarti kehancuran luar biasa yang dapat menghapus Islam dari tanah Andalusia. Gaya bahasa yang ditemukan dalam puisi ini meliputi hiperbola, antonomasia, personifikasi, retorika, oksimoron, paralelisme, pleonasme, eksklamasi, alonim, simbolik, dan tasybih. Selain itu, ditemukan juga wazan, qafiyah, diksi, simbol, nada, pesan, dan hubungan antarunsur dalam puisi tersebut.